Capital endowment and race to the bottom in a federation. Issue 1 (8th April 2018) - Chel, Moumita; Mukherjee, Vivekananda
Abstract : Purpose: This paper aims to analyse the phenomenon of race to the bottom in a federation and provides answer to the question why developing countries are more prone to race to the bottom competition than developed countries. Design/methodology/approach: The paper considers a two-stage game where, in the first stage, two regional governments in a federation choose tax rate on mobile capital employed in its own region by maximising its regional per capita income, and in the second stage, a representative firm chooses capital and labour employment in the two regions by maximising total profit. As capital is mobile across regions, tax policy chosen by any region affects other region. From strategic interaction between the regional governments, the authors derive Nash equilibrium tax rates. Comparing Nash equilibrium with Pareto optimum outcome, race to the bottom is characterised. Findings: The paper finds that federations with poorer endowment of capital are more prone to the race to the bottom outcome. The result is robust to the introduction of different types of asymmetries between the regions and a centrally executed revenue equalisation scheme. Whilst it hints at the fact that capital accumulation can naturally solve the race to the bottom problem, it identifies the presence of an equalisation scheme and equity concern at the regions to weaken the impact of capital accumulation in achieving such an outcome. Originality/value: The role of capital endowment in the race to the bottom literature in fiscal federalism has previously been ignored. This has serious implications for developing countries like China and India where states compete with each other for attracting private capital in their own jurisdictions.